2010
DOI: 10.1038/onc.2010.391
|View full text |Cite|
|
Sign up to set email alerts
|

Dissection of mitogenic and neurodegenerative actions of cystine and glutamate in malignant gliomas

Abstract: Malignant glioma represents one of the most aggressive and lethal human neoplasias. A hallmark of gliomas is their rapid proliferation and destruction of vital brain tissue, a process in which excessive glutamate release by glioma cells takes center stage. Pharmacologic antagonism with glutamate signaling through ionotropic glutamate receptors attenuates glioma progression in vivo, indicating that glutamate release by glioma cells is a prerequisite for rapid glioma growth. Glutamate has been suggested to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…In exchange, cysteine is taken up into tumor cells via the same transporter as antiport34. Further, suppressed transporter expression leads to reduced glutamate export and levels in the extracellular space, and glutamate accumulates intracellular in tumor cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In exchange, cysteine is taken up into tumor cells via the same transporter as antiport34. Further, suppressed transporter expression leads to reduced glutamate export and levels in the extracellular space, and glutamate accumulates intracellular in tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since these target genes are often ubiquitously expressed, the problem naturally lies in the ability to modulate them in a specific manner in cancer cells without disturbing generally the physiological homeostasis. We identified xCT as a target gene playing a decisive role in the progression of malignant gliomas1734. Due to its ubiquitous expression, it falls under the restrictions attendant to target genes and would therefore have limited therapeutic scope.…”
Section: Discussionmentioning
confidence: 99%
“…We describe here a bridge technique, i.e. the organotypic glioma invasion model (OGIM), which combines the advantages of in vitro assays with that of the organotypic brain environment as an in vivo situation [98]. The OGIM is a robust in vitro assay enabling the investigation of key events of tumor angiogenesis within the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover a high-density microvessel network is produced via tumor-induction. The organotypic brain slice model represents the tumor microenvironment in vitro in a three-dimensional culture [98], which is biologically more relevant, but technically more challenging than migration, proliferation and cytotoxic assays being an appropriate possibility to test and optimize anti-cancer compounds.…”
Section: The Organotypic Glioma Invasion Model (Ogim)mentioning
confidence: 99%
“…10 It should be noted, however, that other studies showed no effect of cell proliferation when glioma cells were treated with AMPA receptor antagonists. 41,47 Despite these contradictory results, it is possible that protection from glutamate transporter overexpression in the peritumoral tissue could be due to decreased tumor AMPA receptor activation in addition to protection against AMPA and NMDA receptor–mediated excitotoxic cell death in noncancerous tissue. This hypothesis is further confirmed by the study described above showing increased survival in patients treated with AMPA receptor antagonist talampanel when combined with radiation therapy and chemotherapy (temozolomide).…”
Section: Discussionmentioning
confidence: 99%